(3GdEaUGM Yf eYGfi GdUMGMs - (3jMji Hf (B((3gHjQI Hf(B) (3eMeO Hf gHjQI GdPgdj GdTjHGfqj, CHh GdeXaQ, Yhf GdOjf,J (B560 (3g` s
(3ChdgG (B:s
(3ef GdMOjK GdKdGKjf ef eSfO GHf YHGS bhdg (B: (3bGd cGf GdfHi Udi Gddg Ydjg hSde EPG bGe ef Gddjd jJgLO bGd Gddge QHfG hdc GdMeO CfJ bje GdSehGJ hGdCQV hef ajgf s
(3BNQgG (B:s
(3hajg Odjd Ydi MSf Ndbg hcQe SLjJg hajg LhGR aYd eKd gPG GdYGde hGdUGdM hGdeSde JHQckG Hg aLR GdLRA GdKGdK HMeO Gddg s
(3HgG BKGQ JbWjYs
(3HgG fXGe GdJYbjHIs
(3UaMI GdZdGa eMdGI HGdPgHs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs